2019
DOI: 10.1080/00450618.2019.1661513
|View full text |Cite
|
Sign up to set email alerts
|

Forensic dentistry and disaster victim identification (DVI) in Indonesia

Abstract: The forensic dentist plays an important role in the disaster victim identification (DVI) operations. The first aim of this study was to explore the opinions of Indonesian dentists on the importance of dental records and the respective awareness of Forensic Dentistry. The second aim was to investigate the basic profile of the Indonesian dentists and their experiences working in the DVI operations. Two web-based surveys (S1 and S2) were sent to 360 Indonesian dentists and 8 Indonesia DVI team members, respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…20 Comparative identity analysis can also be performed with bitewing radiographs. 1,8,21 In the studies conducted by Wenzel et al 22 , and Fridell and Ahlqvist 23 , who conducted research on adults on this subject, it was stated that identification would be made with bitewing radiographs. However, it was suggested that it would be more difficult to diagnose pediatric patients in these studies.…”
Section: The Role Of Oral and Maxillofacial Radiology In Identificati...mentioning
confidence: 99%
See 1 more Smart Citation
“…20 Comparative identity analysis can also be performed with bitewing radiographs. 1,8,21 In the studies conducted by Wenzel et al 22 , and Fridell and Ahlqvist 23 , who conducted research on adults on this subject, it was stated that identification would be made with bitewing radiographs. However, it was suggested that it would be more difficult to diagnose pediatric patients in these studies.…”
Section: The Role Of Oral and Maxillofacial Radiology In Identificati...mentioning
confidence: 99%
“…25 Panoramic radiographs are one of the imaging methods used for identification. 1,21 Panoramic radiograms are very useful in identification because they include a large area in a single image. It is used for age estimation.…”
Section: The Role Of Oral and Maxillofacial Radiology In Identificati...mentioning
confidence: 99%
“…Some institutions in Indonesia, such as the Indonesian National Armed Forces (TNI), police, pilots, and flight attendants, can provide good-quality dental records as antemortem data. However, most Indonesians in rural areas are unaware of the importance of routine dental check-ups and treatments [19,20]. This condition has the potential to complicate the process of identifying victims of mass disasters due to the lack of antemortem dental data.…”
Section: Figure 1 Simple Odontogram and Dental Code In The Personal I...mentioning
confidence: 99%
“…However, studies conducted in the past have revealed that the implementation of good dental record practices in Indonesia is not widespread. Specific institutions in Indonesia, such as the Indonesian National Armed Forces (TNI), police, pilots, and flight attendants, have successfully maintained high-quality dental records, especially for antemortem data purposes [7,8].…”
Section: Introductionmentioning
confidence: 99%